Enhancing Education and Training Effectiveness for Microtrans Public Transportation Crews in DKI Jakarta - Nur Achmad Jabrial; Mardiana Mardiana; Putri Dwi Jayanti; Boy Laksmana; Sukardi Sukardi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research examines the effectiveness of education and training programs for Microtrans public transportation crews in DKI Jakarta, focusing on improving operational efficiency and service quality. Through a mixed-methods approach combining qualitative interviews and surveys, key challenges were identified across six critical indicators: punctuality of training sessions, achievement of training targets, implementation of training outcomes, utilization of training benefits, post-training work performance, and behavioral changes. Findings reveal significant gaps, including delays in training sessions, missed training targets, and difficulties in applying acquired skills on the job. Recommendations include enhancing scheduling systems, aligning curricula with operational needs, and integrating practical training methods to bridge these gaps. Furthermore, fostering a culture of continuous learning and professional development among crews is essential to sustain improvements over time. By addressing these challenges, stakeholders can enhance crew competency, service reliability, and overall public transportation quality in DKI Jakarta